2017
DOI: 10.18203/issn.2455-4510.intjresorthop20172090
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive dynamic hip screw for intertrochanteric fractures: comparison with conventional method and surgical tips

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Intertrochantric fractures of the proximal femur are one of the most common injuries of the elderly. Prolonged duration and peroperative blood loss in this elderly frail population is one of the major problems in using the DHS. We performed minimally invasive DHS (MIDHS) implantation for such patients and compared results with conventional technique, hypothesising better perioperative outcomes.</span></p><… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Still, it is associated with considerable blood loss due to greater soft tissue and muscle dissection in addition to the exposure of the fracture site. 23,30,31 This study evaluated the results of minimally invasive DHS fixation in elderly patients with intertrochanteric fractures and assessed the factors that can affect the functional outcomes. Satisfactory results were obtained in 82.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is associated with considerable blood loss due to greater soft tissue and muscle dissection in addition to the exposure of the fracture site. 23,30,31 This study evaluated the results of minimally invasive DHS fixation in elderly patients with intertrochanteric fractures and assessed the factors that can affect the functional outcomes. Satisfactory results were obtained in 82.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The main benefit of the minimally-invasive technique in relation to the traditional surgery is the reduction in opera-tive time and the lower rate of bleeding, but there is no consensus on the superiority of the technique in terms of the the postoperative recovery of the patients. [8][9][10] The main objective of the present study is to analyze intertrochanteric fractures fixed with the DHS system by comparing minimally-invasive plate ostheosynthesis (MIPO) and the traditional Hardinge access route regarding the postoperative pain index. The secondary goal is to assess whether there is a superiority of the former approach in terms of operative time, blood loss indexes, and the degree of active mobility in the immediate postoperative period (IPOP).…”
Section: Introductionmentioning
confidence: 99%
“…The main benefit of the minimally-invasive technique in relation to the traditional surgery is the reduction in operative time and the lower rate of bleeding, but there is no consensus on the superiority of the technique in terms of the the postoperative recovery of the patients. 8 9 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 A study reported mean surgical duration (53.6±13.6 v/s 77.6±16.19) min, Intra operative blood loss (47.58±23.07 v/s 142.67±57.77) ml and duration of hospital stay (3.2±0.43 v/s 7.7±1.2) days in minimally invasive DHS v/s conventional DHS treated patients respectively. 13 Recently several studies have reported on their application of MIS in DHS fixation for intertrochanteric femoral fracture, but actually there are not well organized, local data of prospective randomized, controlled trials of this combination of techniques. The goal of this study is to provide an efficient and pragmatic surgical technique for surgical decision making to reduce the complications.…”
Section: Introductionmentioning
confidence: 99%